EKONOMI POLITIK PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL: STUDI KASUS KEBIJAKAN PUBLISHER RIGHTS AUSTRALIA TERHADAP GOOGLE DAN FACEBOOK - Bustami, Sirwan Yazid (BHUVANA: Journal of Global Studies, 2024)
Australian news media publishers are facing serious challenges as Google and Facebook emerge as digital platforms in the Australian media industry. They have transformed into the main pillars of media industry as they monopolize distribution and monetization of news content as well as the digital advertising market, thus dominate Australia’s digital market share. Their power and dominance in controlling the flow of information and digital advertising have drawn attention of the Australian government. In response, the Australian government enacted the publisher rights policy through adoption of the News Media and Digital Platforms Mandatory Bargaining Code (NMBC). Google and Facebook reacted strongly against the NMBC and threatened to close the services in Australia. This research aims to explain the reasons behind Australia’s enactment of the publisher rights policy against Google and Facebook. Using the analytical descriptive research methods combined with theory of regulatory mercantilism, concept of digital sovereignty, and concept of intellectual property rights, this study argues that enactment of the publisher rights policy is due to the imbalance of bargaining power between the Australian news media publishers and Google and Facebook. In addition, this policy was enacted due to the reduction in traditional revenue received by the traditional news media publishers as a result of declining advertising revenue, content purchases, and subscriptions that pose a threat to sustainability of Australia’s news media industry. Lastly, the adoption of the publisher rights policy is due to the centralized media power of Google and Facebook which endangers diversity of Australian news media.